Peningkatan Ketrampilan Warga Disabilitas: Peningkatan Omzet Batik Ciprat dengan Pemasaran Digital - Purnomo, Rochmat Aldy; Hartono, Sri; Gunawan, Ivan (Jurnal SOLMA, 2024)
The sale of Batik Ciprat Karangpatihan still uses a simple marketing concept and batik craftsmen still rely on the efforts of the village government in collaborating and accepting orders directly from customers. Apart from that, batik administrators and craftsmen have only been taught the batik production process and do not yet have digital marketing skills using e-commerce platforms, so the turnover of ciprat Karangpatihan batik is still not optimal. This program aims to improve partners' skills regarding digital marketing based on e-commerce platforms as an effort to increase the turnover of Ciprat Karangpatihan batik. The partner of this program is Rumah Harapan Mulya with 50 participants consisting of young people with weak socioeconomic backgrounds, women and people with physical disabilities. The method used is to provide exposure and practice regarding digital marketing based on e-commerce platforms such as Shopee. The results of the program show that with the activities carried out, there has been a change from not having skills regarding digital marketing based on e-commerce platforms as an effort to increase the turnover of Karangpatihan splash batik to understanding and having skills regarding digital marketing based on e-commerce platforms as an effort to increase the turnover of Splash batik Karangpatihan. It can be concluded that there has been an increase in skills regarding digital marketing based on e-commerce platforms as an effort to increase the turnover of Ciprat Karangpatihan batik.